Constitution and its interpretation - Egidijus Kūris (Politologija)
In the article, it is oftentimes referred to the recent (1998) article in this journal by Aleksandras Dobryninas in which (on the basis of Aristotelian theory) the Constitution is defined both as a fundamental law of the state, and as the set of fundamental principles revealed inter alia through the interpretation process. After having stated that "it appears difficult to altercate on the theoretical sagacity of the ideas" postulated in the said article, the author indicates that there is a certain inconsistency which may lead to conclusions negating the given theoretical postulates. It is argued that the stability of the constitutional order should not be understood only in quantitative terms (such as the number of amendments to the "basic text" of the fundamental law) but that the potential of constitutional interpretation should also be taken into account.